A Multi-Stakeholder Collaboration Model in Sustainable Agricultural Waste Management: A Case Study Supporting Organic Farming in Bali - Muliarta, I Nengah; Sri Rahayu, Ni Ketut (Industrial and Domestic Waste Management, 2025)
Agricultural waste management in Bali faced complex challenges due to various obstacles in the transition to sustainable organic agriculture. This research focused on collaborative models among stakeholders involved in agricultural waste management. The aim of this research was to explore collaborative models for stakeholders in agricultural waste management that aligned with the journey towards organic farming. This research used a qualitative descriptive method, including a literature review and field observations to identify challenges and opportunities. The results indicated that the Sustainable Organic Circle Model could improve waste management efficiency, reduce greenhouse gas emissions, and enhance soil fertility. The issue of agricultural waste in Bali (rice straw, horticultural waste, livestock waste) was the most critical, but at the same time, it had great potential for sustainability, particularly through composting, animal feed, and biogas production. Current practices were still dominated by crop residue burning due to a lack of knowledge, facilities, and financial constraints. The Integrated Farming System Program and collaboration among stakeholders (including government, NGOs, and academics) were ongoing, but still faced challenges such as limited farmer knowledge and unintegrated policies.